Exploring the Relevance of Inclusive and Universal Design in Islamic Architecture Principles - Subagya, Moch. Restu; Aristawati, Yolandita; Sholihah, Arif Budi (Departement of Architecture, Universitas Islam Indonesia, 2025)
Fifteen percent of the world's population is disabled. Eighty-two percent of them are in developing countries and live below the poverty line due to access limitations. Muslims, as the majority in developing countries, have a vital role in supporting individuals with disabilities through accessible designs. Applying Inclusive Design principles (IDP) and Universal Design principles (UDP) to architectural design can be a solution. This study examines the relevance of IDP and UDP to the Islamic Architecture Principles (IAP). The research method was carried out by collecting IAP, IDP, UDP, and islamic evidence through literature, then formulated into tables to analyze their relevance. The results show that UDP and IDP are relevant to IAP as long as the application emphasizes accessibility, social justice, and diversity of user needs based on Islamic norms without applying the ideology. Hopefully, this research can encourage Muslim communities worldwide to apply UDP or IDP to their designs. Keyword: Inclusive Design Principles; Islamic Architecture Principles; Relevance; Universal Design Principles